2019
DOI: 10.1002/macp.201900200
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkably Large Phase‐Transition Effect in a Random Copolymer of Oligo(ethylene glycol) Methyl Ether Methacrylate (OEGMA)500 Induced by the Photochemistry of the 2‐(Hydroxyimino)aldehyde Group

Abstract: The effect of UV irradiation on the cloud points (CP) of aqueous solutions of a random 1:1 copolymer of oligo(ethylene glycol) methyl ether methacrylate (OEGMA500) and a 2‐(hydroxyimino)aldehyde (HIA) functionalized methacrylate is presented. CPs are determined by visible spectroscopy and dynamic light scattering (DLS). 1H and 13C NMR experiments are carried out in D2O and DMSO‐d6 on the polymer and on an HIA‐functionalized model of the photoresponsive repeat unit. UV‐irradiated solutions exhibit an unprecede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Smith et al 162 achieved higher order morphologies and electric field‐responsive (electrophoretic) nano‐objects by including a cationic monomer in the shell copolymer. Hydrophilic random copolymers exhibiting light‐sensitive cloud points 2,163 may be used as block constituents in more complex architectures. On the other hand, when a light‐sensitive moiety is located in the hydrophobic micellar core, the nanoaggregate can be photo‐stimulated to disassemble or modify its LCST.…”
Section: Random‐ Block‐ and Random‐block Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al 162 achieved higher order morphologies and electric field‐responsive (electrophoretic) nano‐objects by including a cationic monomer in the shell copolymer. Hydrophilic random copolymers exhibiting light‐sensitive cloud points 2,163 may be used as block constituents in more complex architectures. On the other hand, when a light‐sensitive moiety is located in the hydrophobic micellar core, the nanoaggregate can be photo‐stimulated to disassemble or modify its LCST.…”
Section: Random‐ Block‐ and Random‐block Copolymersmentioning
confidence: 99%
“…As an alternative to the creative assembling of readily available monomers to obtain copolymers endowed with multiple responsivity or to introducing specific functionalities by post‐polymerization reactions, many research groups resort to the synthesis of monomers containing functional groups with specific tasks and then copolymerize them with readily available ones. In some cases, the novel monomer is responsive to more than one stimulus 2,214–221 . This approach entails advantages and difficulties.…”
Section: Specially Designed Monomers For Msr Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the photoreactions of oxime and carbonyl compounds have been attracting a renewed attention in contemporary applications, such as the manipulation of soft materials properties [12] and synthetic photochemistry and photocatalysis [13] . For instance, we recently showed that the photochemistry of the HIA group has a remarkably large impact on the physico‐chemical behavior of aqueous solutions of copolymers of OEGMA and an HIA‐functionalized methacrylate [14] . Applications of the HIA to CBO photoisomerization can be envisaged in metal ligation and sensors [15,16] .…”
Section: Figurementioning
confidence: 99%
“…Within the framework of our continuing investigation of the 2-(hydroxyimino)­aldehyde (HIA) functionality, as a versatile structure in multistimuli-sensitive polymers, we have been studying the physico- and photochemical properties of several HIAs. …”
Section: Introductionmentioning
confidence: 99%